Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1194/jlr.m044156
|View full text |Cite
|
Sign up to set email alerts
|

Internalized PCSK9 dissociates from recycling LDL receptors in PCSK9-resistant SV-589 fibroblasts

Abstract: Secreted PCSK9 binds to cell surface LDL receptor (LDLR) and directs the receptor for lysosomal degradation. PCSK9 is potent at inducing LDLR degradation in cultured liver-derived cells, but it is considerably less active in immortalized fibroblasts. We examined PCSK9 trafficking in SV-589 human skin fibroblasts incubated with purified recombinant wild-type PCSK9 or gain-of-function mutant PCSK9-D374Y with increased LDLR binding affinity. Despite LDLR-dependent PCSK9 uptake, cell surface LDLR levels in SV-589 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…The observation that a portion of internalized PCSK9 is not degraded has been recently reported by us after finding human PCSK9 in liver of mice 4 hours after injection of exogenous human PCSK9 5 . Similarly, a recent study with human fibroblasts has documented that a portion of internalized PCSK9 is diverted from the lysosomal degradation pathway to endocytic recycling compartments 27 . It is unclear whether this mechanism involves dissociation of PCSK9 from LDLR or if it is a route for the coupled recycling for both protein partners.…”
Section: Discussionmentioning
confidence: 95%
“…The observation that a portion of internalized PCSK9 is not degraded has been recently reported by us after finding human PCSK9 in liver of mice 4 hours after injection of exogenous human PCSK9 5 . Similarly, a recent study with human fibroblasts has documented that a portion of internalized PCSK9 is diverted from the lysosomal degradation pathway to endocytic recycling compartments 27 . It is unclear whether this mechanism involves dissociation of PCSK9 from LDLR or if it is a route for the coupled recycling for both protein partners.…”
Section: Discussionmentioning
confidence: 95%
“…On the basis of our data alone, however, it remains unclear whether the HLM-dependent mechanism also requires PCSK9:LDLR binding or the presence of the LDLR itself. It is tantalizing to conjecture that HLMs may offer a way to shuttle PCSK9 into an endocytic vesicle without the need for the PCSK9:LDLR interaction, whereby PCSK9 can then direct itself into acidified endosomes (50,59) and induce an interaction with the LDLR via its cysteine-histidine rich domain, which has known affinity for the LDLR at lower pH (60,61). This could effectively bypass the need for the interaction between the PCSK9 catalytic and the LDLR EGF-A domains at the cell surface (50).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism leading to these effects of PCSK9 are unknown. We, and others, have shown that a portion of PCSK9 entering the cell with LDLR remains intact and does not undergo lysosomal degradation for several hours (21, 75). A mechanism to explain how PCSK9 is able to alter intracellular processes is presented in Figure 2.…”
Section: Introductionmentioning
confidence: 95%